Does sleep protect against oxidative stress? - Krebbers, A (2024)
Sleep is a vital behaviour, and despite spending one third of our lives asleep, we are yet to define its function. A proposed function connects sleep and the build-up of reactive oxygen species (ROS) in the brain, suggesting that sleep is needed as antioxidant defence mechanism. Indeed, ROS accumulation is implicated with prolonged waking, and artificial increase of ROS in the brain can induce sleep in animals. Using the fruit fly Drosophila melanogaster, investigated sleep’s possible role as an antioxidant defence. Acting as a ROS sensor in sleep-promoting dorsal fan-shaped (dFB) neurons is the potassium channel Shaker’s b subunit Hyperkinetic (Hk). Oxidization of its cofactor NADPH causes conformational changes of the channel and thereby modulates dFB neuron activity. dFB neurons could thus act as an early-alert system for rising ROS levels in the brain.